Dairy Cattle Maintenance Management in Raraa Village, East Kolaka Regency - Asminaya, Nur Santy; Bain, Ali; Saili, Takdir; Agustina, Dian; Aka, Rahim; Pratiwi, Arby’in; Afyudi, Bobby; Asni, Nur; Putra, Agus Kurniawan (Jurnal Abdimas, 2024)
Dairy cattle are ruminant livestock that produce milk whose productivity is very dependent on maintenance management. This community service activity aims to increase the knowledge and skills of dairy farmers in Raraa Village, East Kolaka Regency. This activity was carried out in several stages, including: 1) Socialization of dairy cattle development; 2. Demonstration on the maintenance and feeding of dairy cows; 3. Monitoring and Evaluation. During the socialization activities, the breeders were very enthusiastic in listening and active in the discussion because the breeders in Raraa Village were just getting to know and starting to raise dairy cows. Farmers are also very focused on paying attention to explanations and technical guidance on the maintenance, management and feeding of dairy cows during direct visits to the breeder's pen. At the end of the activity, an evaluation was carried out to determine the level of understanding of dairy farmers. Monitoring and assistance to farmers is also carried out to help farmers who experience difficulties in the process of caring for and feeding dairy cows. This activity can increase the knowledge and skills of dairy farmers so that farmers can maintain and develop dairy cattle in accordance with the government's goal of distributing dairy cattle seeds in the Southeast Sulawesi region